The Influence of Product Quality, Sales Promotion, and Brand Equity on Customer Loyalty Level : Case Study on PT. Krama Yudha Ratu Motor Jakarta - Neng Siti Komariah; Pratiwi Nila Sari; Misbahul Anwar; Andrian (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study is to determine how far the influence of Product Quality, Sales Promotion and Brand Equity on the Level of Consumer Loyalty using a quantitative approach, data collection using questionnaires, data that has met the validity test, reliability test, and classical assumption test. Through the F test, it can be seen that product quality, marketing strategy, and promotion are worthy of testing brand variables. While the data analysis used multiple linear regression analysis. The results of the study showed that the most positive and significant influence on the level of Consumer Loyalty is Product Quality, Sales Promotion, and Brand Equity. PT. Krama Yudha Ratu Motor must continue to maintain what has been considered good and continue to improve to fix anything that is considered less good.